PUBLIC SPEAKING SKILLS IN EDUCATION IN THE 21ST CENTURY: A SYSTEMATIC LITERATURE REVIEW - Khoirunisa, Amelia; Pratama, Andika Cahya (CV. Global Aksara Pers, 2024)
The ability to clearly articulate ideas and engage an audience is not only essential for academic success, but also for future professional endeavors. Therefore, the development of public speaking skills is an integral part of the educational landscape. This study aims to evaluate the importance of public speaking skills in the context of 21st century education by conducting a systematic review of relevant literature. Using a Systematic Literature Review (SLR) approach, this research analyzes various studies that address public speaking from the perspective of educators and learners. The database used for this review was Google Scholar, which provides access to a wide range of scholarly articles. A total of 9 articles published between 2020 and 2024 were included in this analysis, based on specific inclusion criteria. The search strategy used keywords such as “educators‘ public speaking skills” and “learners’ public speaking skills.” Thematic data analysis techniques were used to identify key themes in the selected literature. The results showed that public speaking skills play an important role in improving the quality of learning. Educators with strong public speaking skills can foster a more interactive learning environment, motivate students and deliver materials effectively. For learners, public speaking contributes to the development of self-confidence, critical thinking and communication skills. However, there is a noticeable gap in research regarding the development of public speaking skills among educators. This research underscores the need for sustainable and integrated training programs to meet the needs of educators in improving their communication competencies. The new findings in this study resulted in 3 important points, namely the need to be an important point in public speaking for educators, namely as a Motivator, Catalyst, Facilitator.